(untitled) (Research, Society and Development, 2022)
The Bordeaux grape variety is the most used in the production of red juices. The objective of the work was to evaluate carotenoids, flavonoids, vitamins C, E and B complex, total fatty acids, phytates, tannins, antioxidant capacity, total phenolic compounds and centesimal composition in whole (W) and defatted (D) Bordeaux grape seed flours and oil (O). Total fatty acids were evaluated by gas chromatography (flame ionization detector). Analysis of vitamins E and complex B were performed by High Performance Liquid Chromatography (HPLC) (fluorescence detection). Vitamin C, carotenoids and flavonoids were evaluated by HPLC (diode-array detection). The fatty acid composition showed the pattern: C18:2>C18:1>C16:0>C18:0. W and D showed higher concentrations of B complex vitamins than O. W had the highest concentration of lutein and total carotenoids, followed by O and D. O presented increased vitamin E and lower levels of flavonoids and antioxidant capacity. The different grape products affected the occurrence and concentration of bioactive compounds.